Sistem Pendukung Keputusan Kelayakan Pemberian Kredit Nasabah Dengan Metode Electre - Marlin Lasena; Sulistiawati Rahayu Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
PT Hasjrat Abadi has collaborated with a financing institution to provide opportunities for vehicle ownership through credit facilities. The credit system offered by the financing institution can boost vehicle sales. However, before that, the lender must conduct a thorough consumer data analysis. This is crucial to ensure that potential customers can repay the approved vehicle loans, thereby avoiding the risk of loan defaults in the future. The process of consumer data analysis is time-consuming due to the abundance of documents involved. Additionally, field surveys are necessary to validate consumer data by applying the 5C Bank Principles (character, capital, capacity, collateral, and condition). Research Objective By implementing the Electre (Elimination and Choice Translation Reality) method in the decision support system, we can provide quick, accurate, and precise information to determine whether potential customers are eligible to purchase vehicles from PT Hasjrat Abadi through credit. This method utilizes the 5C Bank Principles (character, capital, capacity, collateral, and condition) to evaluate consumers. The method used is Research and Development (R&D), which aims to develop specific products and test their effectiveness. The research findings indicate that this system can enhance the services provided to customers at PT Hasjrat Abadi's branch in Gorontalo. Based on the data input by credit analysts, it was found that only 50 percent of the total potential customer data could be approved using the Electre method for credit applications. This facilitates faster, more accurate, and more reliable decision-making for customers.